Development of film statistic in improving the mathematical literacy skill of grafde viii students - Kharisma Aini; Ari Indriani; Dwi Novianti (Universitas Muhammadiyah Lampung, 2026)
Mathematical literacy is one of the key competencies students must possess in 21st-century learning, as it helps them understand, analyze, and solve problems in everyday life. However, students’ mathematical literacy remains relatively low. This is evidenced by the 2022 PISA score of 366, which falls into the “low” category, as well as a 6.7-point decline in numeracy achievement in the 2025 Education Report Card at Kedungadem Public Junior High School 1. Furthermore, the use of interactive learning media in mathematics instruction remains suboptimal, resulting in a gap between the demands of mathematics literacy-oriented learning and actual classroom practices. This study aims to develop FILM (Interactive Mathematical Literacy Flipbook) media for statistics material that is valid, practical, and effective in improving the mathematical literacy skills of eighth-grade students. This study uses the Research and Development (R&D) method with a 4D development model modified to 3D, namely define, design, and develop. The research subjects were eighth-grade students in Class H at SMP Negeri 1 Kedungadem. Research instruments included a validation sheet, a response questionnaire, interviews, and a mathematical literacy skills test. Data analysis was conducted using both quantitative and qualitative descriptive techniques. The results showed that the FILM medium was rated as “highly valid,” with a validity score of 0.911 from the media expert and 0.933 from the content expert. The medium’s practicality, as assessed by teacher responses, was rated at 92%, and by student responses at 82%, both falling into the “highly practical” category. The effectiveness test results showed an N-Gain value of 0.68, classified as moderate. Thus, the FILM medium was deemed valid, highly practical, and sufficiently effective, making it suitable for use as an alternative interactive learning medium to support the improvement of students’ mathematical literacy in statistics. These findings contribute to the development of innovative, technology-based mathematics instruction aimed at enhancing students’ mathematical literacy.